PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI DESA KAMAL KECAMATAN BULU KABUPATEN SUKOHARJO - Bulan Amanda, Trisya Jenys; Winduro, Wirid (Solidaritas, 2025)
The Community Based Water Supply and Sanitation Program (PAMSIMAS) plays an important role in improving access to clean water and sanitation in rural areas. Kamal Village, Bulu District, Sukoharjo Regency faces the problem of limited clean water due to unfavorable geographical conditions, especially during the dry season. The PAMSIMAS program comes as a solution with a community empowerment based approach. The purpose of this study is to analyze and describe community empowerment in the PAMSIMAS program in Kamal Village. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldana (2014) model, including data reduction, data presentation, and conclusion drawing. Sutrisno's (2005:18) community empowerment theory was used to assess the success of the program based on five main indicators: bottom up planning, participation, sustainability, integration, and social and economic benefits. The results showed that community involvement was quite active in the planning and construction stages of the facilities, but declined in the maintenance stage. The main obstacles faced are limited funds and low community awareness in maintaining clean water infrastructure. Nevertheless, the PAMSIMAS program in Kamal Village has had a positive impact by increasing access to clean water and providing social and economic impacts for the community. Although there are still obstacles in implementation, the PAMSIMAS program in Kamal Village has demonstrated a fairly good management structure, positive community involvement in the early stages, and coordination between the community and stakeholders. Therefore, further efforts are needed to increase community awareness and participation in facility maintenance so that the program can run optimally and sustainably. Keywords: Program, PAMSIMAS, Community Empowerment